Divine Violence and Divine Sovereignty: Kierkegaard and the Binding of Isaac - Lee, Hanull (My University, 2015)
This thesis examines the concept of sovereignty, as developed by the jurist Carl Schmitt, and argues that this concept helps to elucidate the very core of Fear and Trembling, a text that continues to be heavily misunderstood despite its great fame in Western thought today. Through a close examination of Schmitt’s formulation of the concept of sovereignty and the method by which he develops this concept through Kierkegaard’s concept of the exception in Repetition, I show how Kierkegaard influenced Schmitt and also how Schmitt’s interpretation is useful for reading Fear and Trembling. However, I also show how Schmitt’s usage of Kierkegaard, despite its ingenuity, is misleading, and present a more faithful reading of Kierkegaard’s concept of exception. With this reorientation, I in turn critique Schmitt’s methodology and the way he understands sovereignty. Following this reinterpretation of sovereignty, I examine the text of Genesis 22 and Fear and Trembling and examine the theological themes that ground the narrative of the Binding of Isaac. I argue that the problem of the Binding and the arguments set forth in Fear and Trembling cannot be understood adequately without a clear awareness of the image of reality that is presupposed. Here, I make use of Erich Auerbach’s illuminating reading of Genesis 22, and Jacob Taubes’ understanding of eschatology. I then examine the problem of violence as presented in the Binding, and how Kierkegaard departs from both Kant’s and Hegel’s critique of Abraham. Finally, I examine Derrida’s reading of Fear and Trembling in The Gift of Death and the way he challenges the height of sovereignty that is implicit within Kierkegaard’s “absolute relation to the absolute.”
Keywords: Kierkegaard; Carl Schmitt; sovereignty; exception; Jacob Taubes; Erich Auerbach; Jacques Derrida; eschatology; political theology; Political Theology; Fear and Trembling; Binding of Isaac; Akedah; The Gift of Death; Repetition; Abraham; theology